Soluble lectin-like oxidized low-density lipoprotein receptor-1 predicts premature death in acute coronary syndromes: clinical research : vascular biology and medicine - Kraler, Simon; Wenzl, Florian A; Georgiopoulos, Georgios; Obeid, Slayman; Liberale, Luca; von Eckardstein, Arnold; Muller, Olivier; Mach, François; Räber, Lorenz; Losdat, Sylvain; Schmiady, Martin O; Stellos, Konstantinos; et al. (European heart journal, 2022)
The lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) and its shedding product [soluble LOX-1 (sLOX-1)] are implicated in atherosclerotic cardiovascular disease (ASCVD) pathogenesis. Herein, we examined the relationship of sLOX-1 with both fatal events and plaque progression in patients with acute coronary syndromes (ACS).Plasma sLOX-1 was assessed at baseline in ACS and chronic coronary syndrome (CCS) patients prospectively recruited in the multicentre SPUM-ACS study, with sex- and age-matched healthy subjects serving as additional controls (n = 2924). Compared with both CCS and controls, ACS patients showed markedly elevated sLOX-1 levels (median, 2.00 and 2.00 vs. 35.08 pg/mL; P < 0.0001) which were independently associated with increased mortality risk over 30-day [tertile (T)3: adjusted hazard ratio (HR), 3.11; 95% confidence interval (CI), 1.44-10.61; P = 0.0055] and 1-year intervals (T3: adjusted HR, 2.04; 95% CI, 1.19-3.92; P = 0.0098). Results remained consistent after adjustment for GRACE 2.0 (T3: adjusted HR, 1.86; 95% CI, 1.04-3.74; P = 0.0391) and were primarily driven by the pronounced relationship of sLOX-1 with cardiovascular mortality at 30 days (T3: adjusted HR, 3.81; 95% CI, 1.62-19.62; P = 0.0036) and at 1 year (T3: adjusted HR, 2.29; 95% CI, 1.19-5.34; P = 0.0148). In ACS patients undergoing serial intracoronary imaging and statin therapy, sLOX-1 dropped significantly in those with coronary plaque regression at 1 year (ΔsLOX-1: −4.64 ± 1.80; P = 0.0057), and showed a good discrimination for predicting plaque progression (area under the curve = 0.74; 95% CI, 0.59-0.86; P = 0.0031).Plasma sLOX-1 levels are increased during ACS and predict fatal events beyond traditional and emerging risk factors. Persistently high sLOX-1 associates with coronary plaque progression in patients with established ASCVD.NCT01000701.
Artikel vorab online veröffentlicht: 24. März 2022
Gesehen am 17.09.2024